THE ROLE OF DEVELOPMENT COMMUNICATION IN NIGERIAN NATIONAL INTEGRATION - JIBRIN UMAR OMACHI (International Studies Journal)
This study attentively focuses on the domains of the roles of Development Communication in National Integration and Development in Nigeria. No nation of the world can attain national cohesion and holistic national development without a crave for Development Communication strategies. This study examines the challenges of Development Communication and stresses out the pertinence of Development Journalism in Nigeria as a democratic nation. It equally examines the development communication approaches to enhance national integration and development in the country. It looks at the social media in enhancing effective communication process for national integration and development which provides the way forward in Nigeria. The study adopts Development Media Theory as the philosophical background for the study. It uses qualitative research approach and focuses on secondary materials for data generation and analysis. The study concludes that the government does not recognize Development Communication role to actively deploy strategies for national integration and development in the country. It amongst others recommends that development communication experts be duly recognised and be made relevant in policies and programmes of the government regarding national integration and development of Nigeria.